Experimental investigation of prefabricated beam-to-column steel joints for precast concrete structures under cyclic loading. (15th April 2020) - Li, Zuohua; Qi, Yihe; Teng, Jun
Highlights: A prefabricated steel joint for precast concrete structures was proposed. Three PSJ specimens and a MJ specimen were cyclically tested. Location of the plastic hinge in the beam was controlled. The performance of PSJ specimens were improved due to the mild steel dampers. Abstract: In this study, a novel prefabricated beam-to-column steel joint suitable for precast concrete structures was developed. The proposed steel joint with dampers could replace cast-in-situ concrete beam-to-column joints in precast concrete structures. Low-yield-point (LYP) steel was selected for the damper to provide the energy dissipation capacity. The plastic hinge location of the beam can be controlled within the joint by the energy-dissipation segments (EDS) made of the LYP 100 steel. Compared with the monolithic joint, the joint is easier to fabricate and take less time during construction while ensuring satisfactory construction quality. Experimental tests were conducted to evaluate the seismic performance of steel joints subjected to cyclic loading. The effects of the thickness of the non-energy-dissipation segments (NEDS) and the length of the EDS were investigated. The test results showed that the proposed steel joint exhibited better hysteretic performance and higher energy dissipation and ductility than a monolithic joint. The joints had sufficient initial stiffness. In addition, an increase in the thickness of NEDS results in higher strength and lower energy dissipation of the PSJ specimens. The strength decreases and the energy dissipation increases with the increasing of the length of EDS.